Cultivating Discipline in Students Through The Application Of Kobimtaq in Class IV At MIMA 29 Miftahul Ulum Ambulu Jember - Elga Yanuardianto; Muhammad Ilyas; Muhammad Fawwaz Al Karim (FALASIFA : Jurnal Studi Keislaman, 2022)
The purpose of this study was to identify and describe the method of establishing student discipline. Additionally, it would be helpful to be aware of how Kobimtaq was used in class IV at MIMA 29 Miftahul Ulum Ambulu to foster student discipline. As we all know, education currently places a strong emphasis on these three development goals: skills, knowledge, and attitudes. Promotion of character education is one method to change students' perspectives. One of the characteristics emphasized in character education is discipline, and MIMA 29 Miftahul Ulum is one of the madrasas that places a strong priority on the discipline of its students. Even the tiniest issues with discipline are handled very seriously at MIMA 29 Miftahul Ulum. In terms of discipline, the students are managed by MIMA 29 Miftahul Ulum using the contact book for religious guidance and piety (Kobimtaq). This research uses a qualitative research type approach with a descriptive type. Data collection techniques there are three ways, namely: observation, interviews and documentation. The findings of this study might be interpreted as indicating that MIMA 29 Miftahul Ulum pupils were pleased with the Kobimtaq book, which was used to manage student behavior. No students voiced opposition to the use of this Kobimtaq book, which may indicate the effectiveness of using Kobimtaq to impose discipline in students and act as a media bridge between instructors, students, and parents. Here, the link is the collaboration imposing student discipline between educators, homeroom educators, the school, and parents of kids. A disciplinary attitude must be ingrained not only in school but also outside of it, so it can be concluded that the Kobimtaq book can assist kids in becoming more disciplined in carrying out activities like praying, studying, reciting the Koran at home, and teaching them honesty.